The Effect Of Using Hello English Application On Students' Ability in Writing Active And Passive Voice At The Eleventh Grade Students Of SMAN 9 Mandau - Camelia, Windy (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2024)
This study was carried out find out. The Effect of Using Hello English Application on Students' Ability In Writing Active And Passive Voice At Eleventh Grade At SMAN 9 Mandau”. The descriptive quantitative was applied to describe data, with a quasi-experimental research design. The study population was all 280 students in grade XI consisting of 9 classes. Due to the large population, the researcher took a sample of 57 students. In this study, the average pre-test score for the experimental class was 63.86 and the control class was 60.57. Meanwhile, the average post-test score of the experimental class was 76.55 and the control class was 68. It can be concluded that there is a difference in the average of students' speaking ability during the pretest and posttest. This means that there is a significant influence on students' writing ability through the Hello English Application.